2021
DOI: 10.3390/molecules26040944
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Target ADAM17 in Disease: From Its Discovery to the iRhom Revolution

Abstract: For decades, disintegrin and metalloproteinase 17 (ADAM17) has been the object of deep investigation. Since its discovery as the tumor necrosis factor convertase, it has been considered a major drug target, especially in the context of inflammatory diseases and cancer. Nevertheless, the development of drugs targeting ADAM17 has been harder than expected. This has generally been due to its multifunctionality, with over 80 different transmembrane proteins other than tumor necrosis factor α (TNF) being released b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 228 publications
(295 reference statements)
2
87
0
Order By: Relevance
“…The remaining targets (TNF, S1P, S1P 2 R, CFTR, and ROCK) may all be functionally linked into a pathological signaling chain (75). Briefly, our previous work shows that soluble TNF [i.e., TNF released via shedding (281)(282)(283)] enhances S1P signaling in cerebral arteries following SAH, by augmenting S1P synthesis and preventing S1P degradation (87,93). Specifically, TNF enhances S1P synthesis via sphingosine kinase 1 activation (284); simultaneously, it reduces S1P degradation, via the downregulation of CFTR protein expression (87,93), a critical S1P transporter (285,286) that sequesters S1P from its receptors (287).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining targets (TNF, S1P, S1P 2 R, CFTR, and ROCK) may all be functionally linked into a pathological signaling chain (75). Briefly, our previous work shows that soluble TNF [i.e., TNF released via shedding (281)(282)(283)] enhances S1P signaling in cerebral arteries following SAH, by augmenting S1P synthesis and preventing S1P degradation (87,93). Specifically, TNF enhances S1P synthesis via sphingosine kinase 1 activation (284); simultaneously, it reduces S1P degradation, via the downregulation of CFTR protein expression (87,93), a critical S1P transporter (285,286) that sequesters S1P from its receptors (287).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, direct injection of TIMP3 in the heart has been shown to downregulate ADAM17's activity by binding to its catalytic domain, thereby inactivating it (74,75). Also, PDIs can directly interact with the MPD of ADAM17, where it catalyzes the isomerization of two disulfide bridges, thus downregulating ADAM17's activity (76,77). A study conducted by Bax et al, revealed that the binding of intergrin α 5 β 1 to ADAM17 via its disintegrin domain, downregulated its activity by affecting its mediated cell adhesion and migration (78).…”
Section: Therapeutic Targets For Ttcmentioning
confidence: 99%
“…EMT can be induced by different extracellular triggers such as various soluble and juxtacrine factors and physical interactions with the ECM through integrin receptors; in addition, the EMT programme can be activated in response to cellular stressors such as hypoxia or therapeutic targets [ 52 , 53 ]. Since ADAM17 mediates the ectodomain shedding of various pro-inflammatory molecules, it is of no surprise that ADAM17 has attracted attention as a potential driver of inflammation and also repurposed pathologically during fibrosis [ 2 , 42 ]. In support of this notion, ADAM17 is overactivated or overexpressed in numerous human chronic inflammatory diseases, and it is noted that EMT represents a convergence point between inflammation and the progression of degenerative fibrotic diseases and cancer [ 2 , 42 ].…”
Section: The Surprising Role Of Adam17 In the Emt Systemmentioning
confidence: 99%
“…Since ADAM17 mediates the ectodomain shedding of various pro-inflammatory molecules, it is of no surprise that ADAM17 has attracted attention as a potential driver of inflammation and also repurposed pathologically during fibrosis [ 2 , 42 ]. In support of this notion, ADAM17 is overactivated or overexpressed in numerous human chronic inflammatory diseases, and it is noted that EMT represents a convergence point between inflammation and the progression of degenerative fibrotic diseases and cancer [ 2 , 42 ]. Several well-designed studies have shown correlations between the increased levels of ADAM17 expression and the severity of fibrosis in patients with degenerative fibrotic diseases.…”
Section: The Surprising Role Of Adam17 In the Emt Systemmentioning
confidence: 99%
See 1 more Smart Citation